2015
DOI: 10.5194/piahs-371-75-2015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing uncertainties in climate change impacts on runoff in Western Mediterranean basins

Abstract: Abstract. This paper investigates the uncertainties linked to climate change impacts on runoff in four mesoscale basins (900 to 1800 km 2 ) in the Mediterranean region. Runoff simulations were based on a daily conceptual model including a snow module. The model was calibrated and validated according to a differential split-sample test over a 20-year period and four competing criterions aiming to represent model structural uncertainty based on the concept of Pareto optimality. Five regional climate models (RCMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The DSST methodology represents the most frequently used method for the diagnosis of model stability and the described evaluation of cross‐calibration and validation over contrasted periods. Furthermore, it provides an approach for temporal transposability of the model parameters over climate‐contrasted periods (Ruelland et al, ; Thirel et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The DSST methodology represents the most frequently used method for the diagnosis of model stability and the described evaluation of cross‐calibration and validation over contrasted periods. Furthermore, it provides an approach for temporal transposability of the model parameters over climate‐contrasted periods (Ruelland et al, ; Thirel et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation of this study is that only different calibration strategies were taken into account in the parameter estimation. It would be more comprehensive to calibrate parameters over different periods, such as wet and dry climate periods [82], as well as by a multi-objective calibration approach [83]. In addition, Seiller et al, [77] showed that the diagnosis of the impacts of climate change on water resources is very much affected by the objective functions used for hydrological model calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although it is commonly acknowledged that the uncertainty resulting from climate modeling (GCMs, gas emission scenarios and downscaling methods) is highest in a context of climate change (e.g., Wilby and Harris, 2006;Arnell, 2011;Teng et al, 2012), it should be noted that the uncertainty stemming from hydrological modeling may also be high. Several authors (e.g., Benke et al, 2008;Brigode et al, 2013;Hublart et al, 2015;Ruelland et al, 2015) showed that the choice of the hydrological model (structural uncertainty) and its parameterization (parameter uncertainty) could cause significant variability in runoff simulations. Consequently, further analyses of the applicability of the model parameters in a nonstationary context and with different calibration criteria are needed before the model is used in future climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3). Many studies have demonstrated the ability of the model to perform well under a wide range of hydro-climatic conditions (e.g., Perrin et al, 2003;Vaze et al, 2010;Coron et al, 2012) and notably in the Mediterranean region (e.g., Tramblay et al, 2013;Fabre et al, 2015;Ruelland et al, 2015). This model relies on precipitation (P) and potential evapotranspiration (PE) and is based on a production function that determines the effective precipitation (the fraction of the precipitation involved in runoff) that supplies the production reservoir and on a routing function based on a unit hydrograph.…”
Section: Hydrological Modelmentioning
confidence: 99%
See 1 more Smart Citation